Effect of hCG hormone administration on estrus induction and reproductive performance of anestrus Iraqi buffaloes (Bubalus bubalis) - Abdulkareem, Talal Anwer; Eidan, Sajeda Mahdi; Al-Sharifi, Sawsan Ali; Al-Mousawi, Seif Mohammed Abd; Dhaydan, Mahroos Neima (Buffalo Bulletin, 2021)
This study was conducted to investigate the influence of human chorionic gonadotropin (hCG) hormone administration on estrus induction and reproductive performance (mating, pregnancy and calving rates) of anestrus Iraqi buffaloes during outbreeding season (May-October). Five hundred and ninety six adult buffaloes of 4 to 6 years old owned by 193 owners within three Iraqi provinces (Baghdad, Muthanna and Thi-Qar) were used in this study. Sixty days post-partum, Four hundred and ninety six buffalo cows were intramuscularly administrated with single 1500 IU hCG injection, whereas the hundred cows were left without any treatment as control group. Estrus rate, as well as mating, pregnancy and calving rates were estimated for each province. Estrus and mating rates were superior (P≤0.05) in buffaloes of Baghdad province (91%), followed by Muthanna (86.37%) and Thi-Qar (81.30%) provinces. Similarly, pregnancy rate was greater (P≤0.05) in buffaloes of Baghdad (85%) and Muthanna (81.63%) than Thi-Qar (67%) provinces. Higher (P≤0.05) calving rate was noted in buffaloes owned by Baghdad owners (82%) as compared with those in Muthanna (79.6%) and Thi-Qar (66%) provinces. In conclusion, hormonal treatment with hCG induced estrus and enhanced reproductive performance of buffaloes during outbreeding season in Iraq. This treatment is practical, easy and low cost, and owners can easily perform it. These improvements were consequently increased owner income ($645=948,000 Iraqi dinar /buffalo) from the sale of more milk.